Integration of Gending Sriwijaya Dance values in group counseling to reduce microaggressions behaviors of junior high - Fasha, Azba Novanda; Atmoko, Adi; Rahman, Diniy Hidayatur; Muslihati, Muslihati (Universitas Negeri Yogyakarta, 2025)
The phenomenon of microaggressions is a manifestation of implicit discrimination that threatens the psychological health of adolescents, with a prevalence of 84% in Southeast Asia and an escalation of 27% in identity-based bullying cases in the 2022–2023 period. This Systematic Literature Review (SLR) aims to analyze the integration of the values of the Gending Sriwijaya Dance as a group counseling modality to reduce microaggression behavior among junior high school students. The methodology used a systematic literature review with the PRISMA protocol and analyzed 15 high-quality articles from the period 2020–2024. The findings identified the intrinsic values of dance, including respect, togetherness, subtlety, and wisdom, that were significantly correlated with the formation of intercultural tolerance. The Gending Sriwijaya dance was chosen in the SLR because it contains a local cultural philosophy that is responsive to the socio-cultural context of Indonesia and has transformative potential in psychological intervention. The group counseling model based on embodied learning through the philosophical and kinesthetic dimensions of dance showed superior effectiveness in enhancing empathy and inclusive behavior compared to conventional interventions. The research contributes by providing an innovative theoretical framework for culturally responsive counseling and recommendations for the development of structured intervention modules as well as multicultural competency training for educational counselors.